Unraveling the mechanobiology of cornea: From bench side to the clinic - Yang, Shu; Zhang, Jing; Tan, Youhua; Wang, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
The cornea is a transparent, dome-shaped structure on the front part of the eye that serves as a major optic element and a protector from the external environment. Recent evidence shows aberrant alterations of the corneal mechano-environment in the development and progression of various corneal diseases. It is thus critical to understand how corneal cells sense and respond to mechanical signals in the context of physiological and pathological conditions. In this review, we summarize the corneal mechano-environment and discuss the impact of these mechanical cues on cellular functions from the bench side (in a laboratory research setting). From a clinical perspective, we comprehensively review the mechanical changes of corneal tissue in several cornea-related diseases, including keratoconus, myopia, and keratectasia following refractive surgery. The findings from the bench side and clinic underscore the involvement of mechanical cues in corneal disorders, which may open a new avenue for the development of novel therapeutic strategies by targeting corneal mechanics.